The effect of combined training program on clinical competence and professional commitment of perioperative nursing students in laparoscopic surgery: a quasi-experimental study - Majid Bagheri; Yaser Adelmanesh; Amirali Alizadeh; Shiva Sadeghi Meymand; Azadeh Amiri; Sahar Khaki (BMC Medical Education)
Abstract Background With rapid advancements in medical sciences, minimally invasive surgical techniques such as laparoscopy have replaced traditional open surgeries. Enhancing the clinical competence and professional commitment of operating room nurses can empower nurses and directly impact surgical outcomes and patient safety. Methods A quasi-experimental pre-test-post-test control group design was employed. Ninety-four students were selected through convenience sampling and randomly allocated to two groups: an intervention group (n = 47) and a control group (n = 47). The intervention group received five sessions for training on laparoscopic surgical principles using E-learning, video demonstrations, and participatory methods. The control group received training using lectures and PowerPoint presentation. Data was collected using a demographic questionnaire, perceived perioperative competence scale- revised (PPCS-R), and the nursing professional commitment scale (NPCS), before and two weeks after the intervention. Results There was no significant difference in the mean scores of clinical competence and professional commitment between the two groups at baseline (P > 0.05). After the intervention, the mean score of clinical competence in the intervention group was significantly higher than the control group (p = 0.005). However, there was no significant difference in the mean score of professional commitment between the two groups after the intervention (P = 0.261). Conclusion Using a combined learning approach in laparoscopic surgery led to a significant increase in the clinical skills of nursing students, resulting in improved performance in the clinical setting. However, to further generalize the results, similar studies with larger sample sizes and in different educational settings are recommended.